Tariff evasion, the trade gap, and structural trade - Ronald B. Davies; Zuzanna Studnicka (University College Dublin, UCD School of Economics, 2022)
While it is well-recognized that there are differences in the trade values reported by exporters and importers, a literature has emerged linking this trade gap to tariff evasion. These efforts, however, lack a structural theoretic underpinning and limit their product-level investigations to a small number of countries. Our first contribution is to provide a structural model of endogenous tariff evasion, one which then highlights the importance of both tariffs and border enforcement. Our second contribution is to use a global, product-level dataset from 2002-2019, the analysis of which is consistent with our model's predictions.
Keywords: F13; F14; H26; 330; Tariff Evasion; Structural Gravity; Trade Gap; Border Controls